2022
DOI: 10.1071/ma22061
|View full text |Cite
|
Sign up to set email alerts
|

Lumpy skin disease: a significant threat to Australia

Abstract: Lumpy skin disease, a mechanically transmitted poxvirus, causes severe disease in naïve populations of cattle and buffalo. It is characterised by development of multifocal cutaneous nodules and systemic illness with significant impacts on animal health, productivity, welfare and trade. Lumpy skin disease entered South-East Asia via Myanmar (November 2020) and later Thailand (March 2021), and has spread rapidly through the region reaching Indonesia in February 2022. This article provides a brief overview of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…While this genetic gradient is largely driven by the capacity of B. indicus genetics to be productive in the harsher environments of tropical and sub-tropical Australia, it may also make the detection of LSDV incursions problematic. It is widely accepted that B. indicus breeds have increased innate resilience to LSDV infections compared to European B. taurus breeds [104,105]. Recently, Sudhakar et al [106] reported on LSDV outbreaks in India with overall 7.10% morbidity (range: 0.75%-38.34%) and 0% mortality in cattle (n = 2,539) from five locations.…”
Section: Implications Of Review Findings To Lsdv Epidemiologicalmentioning
confidence: 99%
“…While this genetic gradient is largely driven by the capacity of B. indicus genetics to be productive in the harsher environments of tropical and sub-tropical Australia, it may also make the detection of LSDV incursions problematic. It is widely accepted that B. indicus breeds have increased innate resilience to LSDV infections compared to European B. taurus breeds [104,105]. Recently, Sudhakar et al [106] reported on LSDV outbreaks in India with overall 7.10% morbidity (range: 0.75%-38.34%) and 0% mortality in cattle (n = 2,539) from five locations.…”
Section: Implications Of Review Findings To Lsdv Epidemiologicalmentioning
confidence: 99%